TEA: transmission error approximation for distance estimation between two Zigbee devices. (3rd January 2011) - Xiao, Weijun; Sun, Yan; Liu, Yinan; Yang, Qing
This paper presents a simple and cost-effective method for distance estimation between two devices. The main idea is to use packet loss estimation, and hence named TEA: transmission error approximation. TEA measures packet loss and uses packet loss statistics to estimate the approximate distance between two Zigbee devices. Both analysis and experiments have been carried out to validate the method. Our field experiments have demonstrated the feasibility and advantages of the proposed method.